Motivations and repercussions regarding crack consumption: the collective discourse of users of a Psychosocial Care Center - Milca Ramaiane da Silva Carvalho; Janaina Raquel de Souza Silva; Nadirlene Pereira Gomes; Magna Santos Andrade; Jeane Freitas de Oliveira; Márcia Rebeca Rocha de Souza (Universidade Federal do Rio de Janeiro, 2017)
Abstract Aim: To identify the motivations and repercussions related to crack consumption by people attending a Centro de Atenção Psicossocial Álcool e Drogas (CAPS AD) (Psychosocial Care Center Alcohol and Drugs) in Bahia. Method: This is a qualitative study developed with eight crack users attending a CAPS AD in a city of Bahia. Interviews, whose content was organized by the technique of the Collective Subject Discourse, were conducted in October and November 2013. Results: The study reveals that the curiosity and the desire to belong to peer groups are events that motivate crack experimentation, and its consumption triggers aggressive and paranoid behavior, depression, financial losses and family and friends abandonment. Conclusion: Given the consequences to social relations and health, actions to prevent the use and consumption of crack are necessary, particularly in order to intervene on the motivations that prompt the first use and relapse.